Teachers' strategies in implementing Content and Language Integrated Learning (CLIL) in the international classroom program of elementary schools - Afifah Marshalina (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
Content and Language Integrated Learning (CLIL) has gained increasing attention in elementary education for its potential to integrate subject learning and foreign language development. However, there is still a dearth of research about the strategic application of CLIL by early education teachers in EFL contexts. This study aims to explore teachers’ strategies in implementing CLIL at elementary schools. This study used a qualitative case study design and involved two elementary school teachers who taught science and math using English. Data were collected through semi-structured interviews, classroom observations, and lesson plan analysis, and then were analyzed thematically. The results showed that the teachers employed five primary types of strategies which include teaching content-specific vocabulary to strengthen students’ subject-related terminology, applying scaffolding techniques, implementing translanguaging, employing active learning, and utilizing multimodal resources. These strategies were employed flexibly to address students’ linguistic limitations while maintaining content objectives. This study contributes to the understanding of how CLIL teachers in early education balance linguistic and cognitive demands in EFL contexts, particularly in Indonesia.